Постановка стратегічних цілей організації у контексті вимог інноваційної конкуренції та стійкого розвитку - Тараненко, І. В. (Видавництво Львівської політехніки, 2011)
На основі узагальнення концепцій конкуренції та інноваційного розвитку запропоновані поняття інноваційної конкуренції та інноваційної конкурентоспроможності. Показано, що в умовах переходу суспільства до глобалізаційно-інноваційної стадії розвитку виникає необхідність розробки гнучких комплексних стратегій, що ґрунтуються на інноваційно-інтеграційному підході. Виокремлено індивідуальні стратегічні цілі (забезпечення добробуту) та загальні, або суспільні стратегічні цілі (стійкий інноваційний розвиток) економічних суб’єктів. Being based at the concepts of competition and innovation development, the author proposes the definition of innovation competition and innovation competitiveness. Proved that under the conditions of transition of the society to globalization – and – innovation stage of development the necessity of working out the flexible complex strategies based at innovation – and – integration strategy arises. The author separated individual strategic goals (well – being provision) and general, or social goals (sustainable innovation development) of economic actors.
Setting of strategic goals of an organization in the context of requirements of innovative competition and sustainable development
Keywords: інноваційна конкуренція; інноваційна конкурентоспроможність; інтегративна взаємодія; стійкий розвиток; стратегічні цілі; innovation competition; innovation competitiveness; integrative interaction; sustainable development; strategic goals